Algebraic Thinking Ability of Seventh Grade SMP/MTs Students on Algebraic Expression Operations Based On Cognitive Style - Iis Syahidah; Mayang Sari (Noumerico: Journal of Technology in Mathematics Education, 2026)
This study aims to describe the algebraic thinking abilities of seventh-grade junior high school students on the algebraic operations material in terms of field-independent (FI) and field-dependent (FD) cognitive styles. This study uses a descriptive qualitative approach with two subjects, namely FI1 (field-independent) and FD1 (field-dependent), selected based on the results of the GEFT test and teacher recommendations. Data were obtained through written tests and interviews and analysed using six indicators of algebraic thinking ability: generalisation and abstraction, analytical and dynamic thinking, modelling, and organisation. The results of the study show that subject FI1 met all indicators well. FI1 could identify important information from the questions, construct mathematical equations accurately, and solve problems using relevant elimination and substitution strategies. He was also able to independently evaluate the results and construct answers in a coherent, logical manner. Meanwhile, subject FD1 showed more limited achievement. FD1 was quite capable of generalizing and abstracting, but there were still errors in copying information. In terms of analytical and dynamic thinking, as well as modelling, FD1 did not demonstrate adequate procedural understanding or verify answers. Nevertheless, FD1 still attempted to organize information and final results in a structured manner